The role of mangrove leaf extract (Avicennia marina) on the healing of angular cheilitis induced by S.aureus and C.albicans in white male rats of wistar strain: Peranan ekstrak daun mangrove (Avicennia marina) terhadap penyembuhan angular cheilitis yang diinduksi S.aureus dan C.albicans pada tikus jantan putih galur wistar - Sumintarti; Ahmad Afizenna; Harlina; Ali Yusran; Erni Marlina; Andi Anggun Mauliana Putri; Israyani; Nur Asmi Usman (Makassar Dental Journal PDGI Makassar, 2022)
Plants are often used as herbal medicines because their active substances have known. Mangrove as herbal medicines are still under-researched; mangrove leafextract can be useful as anti-inflammatory, antibiotic, hemolytic drug, hypoglycemic has been specifically investigated for its inhibitory power againstStaphylococcus aureus as one of the causes of angular cheilitis and shows good results. This true experimental laboratory research with a posttest only control group design used 24 male white rats of the Wistar strain which were divided into group-1 were induced with S.aureus and given mangrove leaf extract, thegroup-2 was induced with S.aureus and given gentamicin, the group-3 was induced with C.albicans and given mangrove leaf extract, and the group-4 was induced with C.albicans and given miconazole. On the third day, wound length in the first group-1 was 0.23±0.2, in the group-2 was 0.00±0.0, in the group-3was 0.21±0.2, and the group-4 was 0.16±0.2. Based on the Friedman test, it showed significant results (p<0.05). It was concluded that mangrove leaf extract accelerated the wound closure process of angular cheilitis induced by S.aureus and C.albicans.